Transformation of Quality Culture in Improving the Quality of Islamic Education Institutions - Robita, Achmad; Fauzi, Fauzi; Dakir, Dakir (International Journal of Education, Culture, and Society, 2025)
Improving the quality of education is an urgent necessity for Islamic educational institutions in responding to global challenges and the demands of the modern era. Transforming the culture of quality is a strategic approach to develop an Islamic education system that is competitive, holistic, and character-driven. This study aims to examine the role of quality culture in enhancing institutional performance and to design effective and sustainable transformation steps. The method used is literature review and descriptive qualitative analysis of best practices implemented in several Islamic educational institutions. The findings reveal that a quality culture grounded in Islamic values such as amanah (trustworthiness), ihsan (excellence), and istiqamah (consistency) contributes to building a learning environment that is religious, collaborative, and responsive to change. The success of quality culture transformation relies heavily on leadership commitment, stakeholder involvement, and the implementation of an integrated quality management system. Therefore, transforming the quality culture not only improves academic performance but also reinforces the spiritual and social missions of Islamic educational institutions in shaping morally upright future generations.